Autonomously Interacting Banks - Yvan Lengwiler; Dietmar Maringer (University of Basel, Center of Business and Economics (WWZ), 2011)
The great financial turmoil that started 2007 has brought bank regulation back into the political debate. There is talk about imposing new regulations on banks and other financial intermediaries. Yet, we are not convinced that it is completely understood how the existing regulation affects systemic stability, let alone what the effect of new proposed rules would be. In order to better understand these issues, we study the interaction of hetero- geneous financial agents in a market that features several properties we believe to be realistic. Our agents develop heterogeneous views about the correct valuation of a risky asset. Some agents (banks) operate with substantial leverage and thus bankruptcy is a possibility. Agents may engage in fire sales, either because they face real financial trouble, or because they are forced to by regulation. Moreover, through their trading activities, agents exert externalities on each other's balance sheets due to mark-to-market. Through this mechanism, fire sales can lead to contagion, and one failing bank can cause several more to follow suit.
Keywords: C63; G21; G28; 330; bank regulation; BIS capital adequacy requirements; Basel II; Basel III; leverage ratio; default rate; systemic stability; fire sales; contagion; autonomous agents; simulation; Basler Akkord; Bankrisiko; Bankenkrise; Ansteckungseffekt; Simulation; Agentenbasierte Modellierung